Performance management in nonprofit organizations global perspectives - Hoque, Zahirul; Parker, Lee D. (Lee David) (Routledge studies in the management of voluntary and non-profit organizations, 2014)
This book collects and presents that evidence for the first time, offering insights to help nonprofits face these new challenges head-on. Performance Management in Nonprofit Organizations focuses on both conventional and contemporary issues facing nonprofits, presenting evidence-based insights from leading scholars in the field. Chapters examine the design, implementation, and working of accounting, accountability, governance, and performance management measures, providing both retrospective and contemporary views, as well as critical commentaries on accounting and performance related issues in nonprofit organizations The book's contributors also offer critical commentaries on the changing role of accounting and performance management in this sector. This research-based collection is an interesting and useful read for academics, practitioners, students, and consultants in nonprofit organizations, and is highly accessible to accounting and non-accounting audiences alike